Applying total quality management principles to faculty selection - Cole, Bryan R. [Verfasser] (My University, 1995)
"This paper outlines a systematic methodology for effecting Total Quality Management in higher education decision making with particular attention to the faculty selection process. Following a brief analysis of the application of TQM to higher education in general and consideration of the contextual and power relations issues associated with implementation of TQM, a model for integrating Total Quality Management principles into the faculty recruitment, identification and selection process is outlined, this model relates the role of vision, mission, planning and organizational design with quality concepts (understanding a system and system theory, leadership, empowerment, client/constituent satisfaction, team building, and continuous process improvement). Drawing upon Marchese and Lawrences's (1987) work wherein they identified eight critical processes in the selection of faculty, one critical process - 'Defining the job' is specifically analyzed using the continuous improvement methodology as an example of the specific application of TQM techniques to higher education decision making. the model ans this example provide educational leaders/search committees with an enhanced framework within which they can effectively analyze an evaluate faculty selection processes, criteria for selection, and relevant contextual issues that will result in the identification and selection of the best qualified faculty available." (author's abstract, IAB-Doku) ((en)) Der Aufsatz befasst sich mit der Anwendung von Prinzipien des Total Quality Management auf Entscheidungsfindungsprozesse im Hochschulsystem, insbesondere bei der Personalauswahl des Hochschulpersonals in den Fakultäten. (IAB)
Anwendung von "total quality management" - Prinzipien auf die Personalauswahl
Keywords: L 6.2.4 Bildungserfolgscontrolling; P 3.2.3 Lehrer; S 5 Organisationsentwicklung; T 3 Forschungsmethoden; Hochschulsystem; Qualitätskontrolle; Lehrer; Hochschullehrer; Berufsproblem; Entscheidungsfindung; Bewerberauswahl; Personalplanung; Qualifikationsanforderung; Management; Methode